2005
DOI: 10.1111/j.1468-3083.2005.01284.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment options – development of consensus guidelines

Abstract: In conclusion, treatment decision-making tools (e.g. an illustrated booklet or CD-ROM presenting each type of onychomycosis and criteria to be considered before selecting treatment regimen) would be valuable supports for the successful treatment of onychomycoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
87
0
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(94 citation statements)
references
References 37 publications
2
87
0
5
Order By: Relevance
“…However, if it fails, or if more than 50% of the nail, including the matrix area, is infected, systemic drugs should be prescribed. According Lecha et al (2005), in these cases, oral monotherapy or a combination therapy is indicated.…”
mentioning
confidence: 99%
“…However, if it fails, or if more than 50% of the nail, including the matrix area, is infected, systemic drugs should be prescribed. According Lecha et al (2005), in these cases, oral monotherapy or a combination therapy is indicated.…”
mentioning
confidence: 99%
“…Amorolfine nail lacquer and oral terbinafine are the most effective drugs as monotherapy. However, the best cure rates are obtained with a combination of oral and local therapy (Lecha et al 2005). Clues to consider: 1.…”
Section: Treatment and Outcomementioning
confidence: 99%
“…Among the zoophilic species most commonly involved in these infections are Superficial mycosis (e.g. Tinea pedis, T. mannum, T. corporis and T. cruris) usually react to topical antifungals 3,11,23 . Among all the three genera of dermatophytes, Trichophyton is most prevalent strain responsible for dermatophytosis.…”
Section: Dermatophytes and Dermatophytosismentioning
confidence: 99%
“…With topical medication, primarily mild skin reactions may occur at the site of application 24 . For patients displaying wide areas of infection or in cases of severe or constant infections, oral therapy should be considered and the same is true for infections caused by T. unguium and T. capitis, where itraconazole, fluconazole, griseofulvin, and ketoconazole are the subjected antifungals to be used 3,23 .…”
Section: Dermatophytes and Dermatophytosismentioning
confidence: 99%